Pola ruang sebaran objek dan fasilitas penunjang wisata berbasis sistem informasi geografis di kawasan Taman Nasional Bali Barat - Barnad, Titan Octalia; Asmiwyati, I Gusti Agung Ayu Rai; Mayadewi, Ni Nyoman Ari (Jurnal Arsitektur Lansekap, 2021)
The West Bali National Park area is a nature protection area that has a conservation function as well as educational tourism. This has boosted enthusiasm for tourist visits, followed by a rapidly increasing development of tourism support facilities in the TNBB area and its buffer villages. However, these developments have not been properly recorded and mapped, so a mapping process is necessary. The method used in this research was a survey with data collection techniques including direct observation, interviews, and literature study. The stages of this research were the identification of tourism support facilities and objects according to the tourism support facilities criteria indicators, analysis, and synthesis. The GIS analysis process used the nearest neighbor analysis approach to study the distribution patterns formed from the distribution of tourism support facilities in the TNBB area. This analysis process produced recommendations for the development of tourism support facilities based on accessibility factors, distance, and the agglomeration theory approach can be used as a basis for regional development, especially in the elements of facilities and infrastructure in the TNBB area.